Supercritical water oxidation and process enhancement of nitrogen-containing organics and ammonia. (15th October 2020) - Li, Jianna; Wang, Shuzhong; Li, Yanhui; Jiang, Zhuohang; Xu, Tiantian; Zhang, Yishu
Highlights: Treatment effects and kinetics of nitrogenous organics and ammonia are summarized. Transformation pathways of different organic nitrogen groups are concluded. Influence of operation parameters on degrading organics are discussed. Different enhancement processes to remove ammonia are analyzed. Suggestions about improving the enhancement processes are put forward. Abstract: Supercritical water oxidation (SCWO), as a promising technology for treating organic wastewater and sludge, has attracted the attention of many scholars. Nitrogen-containing organics are refractory substances that widely exist in industrial waste, and their effective degradation is of great significance to the environment. In this paper, the treatment effects, reaction kinetics, and migration and transformation pathways of various nitrogen-containing organics (amino group, nitro group, mixed group, and nitrogen heteroatom) under SCWO conditions are summarized, and the influences of the reaction temperature, oxidant type and concentration, residence time, and initial concentration of organics on the degradation of organics are also discussed. NH3 -N is the primary intermediate product produced during the oxidation process of the amino group and nitrogen heteroatom organics, and the further degradation of NH3 -N is the limiting step for the whole reaction. This paper focuses on the relevant strengthening technologies used to enhance the degradation of NH3 -N, including heterogeneous catalytic oxidation with reactor wall or metal oxides; co-oxidation with auxiliary fuels such as methanol, ethanol, isopropanol, and glycol; strong oxidation with NO3 − or NO2 − ; and segmented oxidation by multi-injection of oxidants or fuels. In addition, in order to achieve the complete removal of NH3 -N and COD synergistically under relatively mild SCWO conditions, avoid the formation of NOx, NO3 −, and NO2 −, and convert organic nitrogen into environmentally friendly products such as N2 and N2 O, further research requirements and challenges are introduced. Graphical abstract: Image, graphical abstract